Evaluation and characterization of the anaerobic profile in soccer players - Matos, Bruno Jos? Fernandes Faria (2018)
Soccer is the most popular sport in the world and is practiced by both men and women, young people and adults with different levels of specialization. The performance of a soccer player is dependent on the interaction of many factors, such as: technical, tactical, psychological, physiological and biomechanical. In recent years, much research has been conducted on player performance during the game and science has been widely incorporated into training planning. Changes in performance and physiological response throughout the game were studied with a focus on the individual differences in physical stress to which players are exposed in the game.